Intracranial metastases of intramedullary spinal cord low-grade astrocytoma - Sharareh Sanei-Sistani; Ghasem Miri-Aliabad; Hamid Dahmardeh; Mahdieh Montazeran; Mehdi Jahantigh; Mohsen Zare (Indian Journal of Medical and Paediatric Oncology)
This paper reports a case of intramedullary spinal cord low-grade (LG) astrocytoma that developed brain metastases after 21 months. A 6-year-old child presented with lower spine pain and falls during daily activity. A spinal cord mass was detected using spinal magnetic resonance imaging (MRI), and brain MRI was normal. The spinal lesion was partially resected, and pathological findings revealed LG astrocytoma (WHO Grade II). The patient underwent thoracolumbar radiotherapy. He returned 21 months following initial admission with symptoms of nausea, vomiting, headaches, and seizure. Brain MRI revealed multiple intracranial masses at the posterior fossa, left lateral ventricle, cerebellopontine angles, and left Meckel cave. A recurrent lesion was detected in the thoracic and lumbar regions of the spinal cord and in the cauda equina. The patient underwent chemotherapy. This rare case warns practitioners to monitor closely the cases of spinal cord astrocytoma that are diagnosed as LG tumors based on histology.